Penerapan Etika Profesi di Bidang Keamanan Cyber untuk Mencegah Kejahatan Dunia Maya - Idzhand, Aan Nur; Harahap, Alif Irfan; T. Raihan Yudisthira; Amiruddin, Amiruddin (VISA: Journal of Vision and Ideas, 2024)
Cybercrime is currently attracting worldwide attention as a type of international crime. Cybercrime via the Internet is a new type of cybercrime that has emerged as a result of advances in internet technology. This research uses qualitative methodology, which is related to the meaning, concepts, definitions, attributes, metaphors, symbols and descriptions of an object. The research results show that cyber security has an important role in improving information network security. Cybercrime and data privacy and security are closely related fields where ethics and technology interact. When using technology, ethics serves as a guide to reduce adverse impacts on data security and privacy. Data security and privacy go hand in hand with data protection. To prevent cybercrime and maintain data security and privacy, cyber security knowledge is essential. Data security for privacy is not only important, it is also essential for political, spiritual, religious and even freedom of expression. Ethics places great emphasis on protecting data security and blocking genuine, unauthorized access.